PENERAPAN PERSONAL HYGIENE PADA KARYAWAN FOOD AND BEVERAGE SERVICE HOTEL ARYADUTA PEKANBARU - Adi Kurniawan; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
In the world of hospitality especially in food and beverage service every single thing must be considered to give the best food to guest of hotel. Actually not only about food but the first thing seen by guest of hotel before they enjoy their food is about employee. Employee of food and beverage service must be clean in every single thing in their body.Because of that really need knowledge about important thing implementation personal hygiene for the employee. Not only in working area but also in their daily activity so they get used to a healthy lifestyle. Finally a comfortable working atmosphere will be created.Keyword : Hospitality, Health, Personal Hygine, food and Beverage, Life Style